"Less is more": Non operative management of short term superior mesenteric artery syndrome. Issue 4 (December 2015) - Naseem, Zainab; Premaratne, Gamini; Hendahewa, Rasika
Abstract: Introduction: Superior mesenteric artery (SMA) syndrome is a relatively rare aetiology of proximal intestinal obstruction. This is caused by narrowing of vascular angle of SMA and aorta compressing the third part of the duodenum (D3). Predisposing factors may include precipitous weight loss, corrective spinal surgery or repair of an aortic aneurysm. Presentation of case: A 53 year old male presented to our department with worsening post-prandial vomiting and epigastric pain for last three months. One examination, epigastric region was distended with succussion splash on abdominal auscultation. History did not include any predisposing factor. CT scan showed narrow angle of 12.77° between SMA and aorta owing to the compression of D3. Since onset of vomiting and resultant poor oral intake, he had lost 11 kg of his usual body weight. After gastric decompression, nasojejunal enteral feeding was started. Diet was progressed to oral feedings gradually and following return to his baseline weight, he continued to be free of symptoms in follow-up visits. Discussion: Although there are recognised predisposing factors but sometimes aetiology remains idiopathic. SMA syndrome should initially be managed non-operatively with gastric decompression, correction of water and electrolyte imbalance, and hemodynamic instability. Regaining weight helps increasing vascular space between SMA and D3 thus relieving obstruction. Persistence of symptoms beyond 3–4 weeks warrants surgical intervention. Conclusion: Non operative management with nutritional supplementation remains the first line of therapy. Highlights: We present a case of rare superior mesenteric artery syndrome. No apparent predisposing factor was present. Non operative management with decompression and enteral feeding proved to be successful. Non operative management with nutritional supplementation remains the first line of therapy.